Dietary patterns and retinal vascular calibre in children and adolescents with type 1 diabetes. (8th January 2016) - Keel, Stuart; Itsiopoulos, Catherine; Koklanis, Konstandina; Vukicevic, Meri; Cameron, Fergus; Gilbertson, Heather; Brazionis, Laima
Abstract: Purpose: To examine the association between dietary patterns and retinal vascular calibre in children and adolescents with type 1 diabetes. Methods: A hospital‐based cross‐sectional study of 83 children and adolescents with type 1 diabetes was conducted over an 8‐month period. Dietary patterns were extracted using principal components analysis from completed food frequency questionnaires. Retinal vascular calibre was measured by a trained grader using a standardized protocol and later summarized as central retinal artery equivalent (CRAE) and central retinal vein equivalent (CRVE) using a semi‐automated computer program. Results: Three major dietary patterns were identified as follows: (1) processed foods, (2) plant‐based foods and (3) vegetable/fish avoidance pattern. The processed pattern had high component loadings for processed meats and high fat takeaway foods. The plant‐based pattern had high component loadings for a number of fruits including, but not limited to, pineapple, grapes oranges and mangos as well as a smaller number of vegetables, including beans and leeks. The vegetable and fish avoidance pattern had high inverse component loadings for canned and fresh fish as well as a number of vegetables including, but not limited to, pumpkin, green beans, broccoli, sweet potato and cabbage. Adjusted regression analysis revealed the 'vegetable/fish avoidance' dietary pattern was associated with a wider CRVE (ExpB = 3.67, 95% CI = 0.11/7.24, p = 0.039). After multivariable adjustments, a vascular risk profile that included: older age, higher BMI, higher systolic blood pressure, greater gestational age, longer screen viewing time, lower maternal education level, lower physical activity levels and lower high‐density lipoproteins concentrations were more likely to display narrower CRAE (ExpB = −2.43, 95% CI = −4.92/0.06, p = 0.041). Conclusions: This study provides the first evidence for a diet–calibre relationship in children and adolescents with type 1 diabetes. This outcome has potential public health implications, as promotion of healthy eating patterns in children and adolescents might attenuate changes in microvasculature that have been related to an increased risk of microvascular disease, such as retinopathy, in adulthood. Additional studies are warranted to explore and validate this novel finding.